Some Consequences of the Habit of Judging Quality by Price - Scitovszky, Tibor (Review of Economic Studies, 1944)
Journal Article Some Consequences of the Habit of Judging Quality by Price Get access Tibor Scitovszky Tibor Scitovszky Washington, D.C. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 12, Issue 2, 1944, Pages 100–105, https://doi.org/10.2307/2296093 Published: 01 September 1944